A Novel Calcium Phosphate–Based Nanocomposite for Augmentation of Cortical Bone Trajectory Screw Fixation - Wang, Yuetian; Liu, Chun; Liu, Huiling; Fu, Haoyong; Li, Chunde; Yang, Lei; Sun, Haolin (International journal of nanomedicine, 2022)
Purpose: To evaluate the effect of cement augmentation of cortical bone trajectory (CBT) screws using a novel calcium phosphate-based nanocomposite (CPN). Material and Methods: CBT screws were placed into cadaveric lumbar vertebrae. Depending on the material used for augmentation, they were divided into the following three groups: CPN, polymethylmethacrylate (PMMA), and control. Radiological imaging was used to evaluate the cement dispersion. Biomechanical tests were conducted to measure the stability of CBT screws. A rat cranial defect model was used to evaluate biodegradation and osseointegration of the CPN. Results: After cement augmentation, the CPN tended to disperse into the distal part of the screws, whereas PMMA remained limited to the proximal part of the screws (P < 0.05). As for cement morphology, the CPN tended to form a concentrated mass, whereas PMMA arranged itself as a scattered cement cloud, but the difference was not significant (P > 0.05). The axial pullout test showed that the average maximal pullout force (Fmax) of CPN-augmented CBT screws was similar to that of the PMMA group (CPN, 1639.56 [+ or -] 358.21 N vs PMMA, 1778.45 [+ or -] 399.83 N; P = 0.745) and was significantly greater than that of the control group (1019.01 [+ or -] 371.98 N; P < 0.05). The average torque value in the CPN group was higher than that in the control group (CPN, 1.51 [+ or -] 0.78 N*m vs control, 0.97 [+ or -] 0.58 N*m) and lower than that in the PMMA group (1.93 [+ or -] 0.81 N*m), but there were no statistically significant differences (P > 0.05). The CPN could be biodegraded and gradually replaced by newly formed bone tissue after 12 weeks in a rat cranial defect model. Conclusion: The biocompatible CPN could be a valuable augmentation material to enhance CBT screw stability. Keywords: cement augmentation, CBT screws, osteoporotic spine, PMMA, CPN